PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PENCEMARAN NAMA BAIK MELALUI MEDIA SOSIAL - Immanuel Klaudeaz Irlamtio, - (2019)
This thesis aims to find out the factors restricting law enforcement efforts against the perpetrator of the criminal offence of defamation through social media and how form law enforcement against the perpetrator of the criminal offence of defamation through the social media. This thesis based on the case of Tambok Lamhot David who did the libel to Showroom Sky Motor because it felt the Ministry that he got less satisfying. Research methods the compilers do it with yudiris normative approach, i.e. the writing of scientific papers based on the study of librarianship and looking for concepts, opinions or inventions that relate to the problem. The results showed that law enforcement law number 11 year 2008 Of the information and electronic transactions and the book of the law of criminal law relating to social media users in Indonesia in the implementation is not effective even very bad. This is due to the multiplicity of communities of users still social media in Indonesia who conduct in tort law in Social Media due to the limitations of his knowledge of the law of information and electronic transactions (UU ITE) as well as the book Criminal Law (The Criminal Code). Where they think it's just a rule that could easily be broken. As for the factors that influence the penegakannya even slow him down is a factor in the law, law enforcement, factor factor means or facilities, community factors and legal culture.